Prevalence of pathogenic and non-pathogenic intestinal parasites in pregnant women living in poverty and social inequality (2018)
Intestinal parasitism in large urban cities is an ongoing public health challenge. Although most epidemiological studies were concentrating on children, there is an ongoing concern that adult vulnerable populations are prone to protozoal and helminthic pathogenic infestations. In pregnant women living in social inequality settings, this is particularly important as it may affect their overall health and that of their offspring.